1989
DOI: 10.1002/app.1989.070380117
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of acrylamide with cationic monomers in solution and inverse‐microsuspension

Abstract: SynopsisThe free radical copolymerization of acrylamide with three of the most commonly used cationic comonomers diallyldimethylammonium chloride, dimethylaminoethylmethacrylate, and dimethylaminoethylacrylate, the latter two quatemized with methyl chloride, was investigated. The polymerizations were carried out with azocyanovaleric acid and potassium persulfate over the temperature range ,45-60°C. The copolymer reactivity ratios were determined with the errorin-variables method Using residual monomer concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…However, the concentration of monomer is different in polymer aggregate and aqueous droplet. 20 Increasing amphipathic graft copolymer concentration amounts to increasing locally the monomer concentration ([M]n) in polymer aggregates. 21 Moreover, TEM experiments have shown that the size of polymer aggregates increases with increasing amphipathic graft copolymer concentration, which results in an increase in the content of acrylamide in polymer aggregates.…”
Section: 23mentioning
confidence: 99%
“…However, the concentration of monomer is different in polymer aggregate and aqueous droplet. 20 Increasing amphipathic graft copolymer concentration amounts to increasing locally the monomer concentration ([M]n) in polymer aggregates. 21 Moreover, TEM experiments have shown that the size of polymer aggregates increases with increasing amphipathic graft copolymer concentration, which results in an increase in the content of acrylamide in polymer aggregates.…”
Section: 23mentioning
confidence: 99%
“…16 Although the copolymerization of macro monomer 1´ with compound 2 involves two vinylic comonomers, unlike that between monomer 1 and com pound 2 involving the diallylic and vinylic comonomers, macromonomer 1´ (as well as 1) is much less reactive than 2. This is also caused, most likely, by steric hindrance, because macromolecules 1´ are bulky.…”
Section: Resultsmentioning
confidence: 99%
“…These complexes can integrate further with the chain growth radicals from PAM by altering the activity of the radicals and initiating the polymerization reaction. This process improves reaction rate and product viscosity as well [48]. In conclusion, the addition of ATP facilitates AM polymerization.…”
Section: Initial Synthesizing Mechanism Of Atp/pammentioning
confidence: 95%